Race, Gender and Networks in Portfolio Work: Difficult Knowledge - Tara Fenwick; Kiran Mirchandani (Adult Education Research Conference, 2004)
This paper reports findings of our qualitative research exploring the multiple Ways in which race, gender and class processes impact on portfolio work, with particular attention to networking processes